Private Operators and Rural Water Supplies : A Desk Review of Experience - Kleemeier, Elizabeth L. (World Bank, Washington, DC, 2014)
This study examines experiences with using the private sector to manage domestic water supplies serving dispersed populations or very small settlements in rural areas. The potential contribution from private operators is well-known for small towns. The unanswered question is whether private operators are an option for more remote rural areas with low population density. This review therefore focused on operations that: 1) serve dispersed populations or settlements with fewer than 5,000 inhabitants in rural areas, 2) have been undertaken on a significant scale, and 3) engage individuals or for-profit organizations to manage water supplies. The rationale for examining rural private operator models is twofold: sustainability and expanded access. First, rural private operators may offer a solution to the high rates of nonfunctioning water points, especially in rural Africa. Second, private operator models may enable governments to leverage private capital and rationalize government subsidies for rural domestic water infrastructure. Those capacities would enable governments, in turn, to expand access to safe rural domestic water supplies.